Identitas Âzar Dalam Literatur Tafsir Nusantara - Egi Sukma Baihaki (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
Âzar is one character names enshrined in the Qur'an, which appears in the story of Ibrâhîm's preaching dialogue. The figure of Âzar into a debate among historians as well as mufassir. The difference of views regarding the identity of Âzar, closely related to the sources of the Torah, which was used as a comparison to explain the figure of Âzar mentioned in the Qur'an. The identity of Âzar in the end, a debate in the realm of theology, as it pertains to the sanctity of nasab to the prophets. Differences of interpretation regarding the identity of Âzar keeps going, in every time and every interpretation of written. The coming of Islam to the archipelago, at the same time the entrance for everything related to the teachings of religion including knowledge and debate theology. With the method of comparative thematic and theological approach, it can be concluded that, the issue of the identity of the Âzar also developed in the literature the interpretation of the archipelago. There are three views on the identity of Âzar in the literature the interpretation of the archipelago. First, it holds that Âzar was Ibrâhîm's father which included these groups is Hasbi, Hamka was the Tafsir Kemenag RI. Second, it holds that Âzar was Ibrâhîm's uncle, which useudes this group is al-Nawawi and Quraish Shihab. A second view of the exegetes this Archipelago has theological ramifications as it did on the classical exegetes. For those who consider Âzar was Ibrâhîm's biological father, then they are not disputed there was a pagan Prophet who parents, but for those who think that their father is not Âzar theologically they hold on the sanctity of nasab the Prophet spared from the pagan ancestors.